FI--J-supplemented modules - Ali, Abdlkareem; Khalid, Wasan (Iraqi Journal of Science, 2021)
A Module M is called cofinite J- Supplemented Module if for every cofinite submodule L of M, there exists a submodule N of M such that M=L+N with main properties of cof-J-supplemented modules. An R-module M is called fully invariant-J-supplemented if for every fully invariant submodule N of M, there exists a submodule K of M, such that M = N + K with N K K. A condition under which the direct sum of FI-J-supplemented modules is FI-J-supplemented was given. Also, some types of modules that are related to the FI-J-supplemented module were discussed.